IMPACT OF CLIMATE CHANGE CONCERN ON ENTREPRENEURIAL INTENTION - Doğu KAYIŞKAN; Esin ASLANPAY; Esin CANDAN; Serpil ÜNAL KESTANE (Prizren Social Science Journal, 2024)
As a country significantly vulnerable to the impacts of climate change, Turkey made an ambitious climate change commitment by ratifying the Paris Agreement in October 2021 and set a target of net zero emissions by 2053. Both climate change and the targets set by our country in this context make the issue important in terms of sectors and entrepreneurship. In this study, the effect of climate change on entrepreneurial intention was examined. The study aims to analyze the perceptions of active and potential entrepreneurs about climate change concerns and reveal the effects of the said concern on entrepreneurial intention.